Chapter Progress in Polymer Thermoelectrics - Tkachov, Roman (InTechOpen, 2016)
This chapter focuses on the relationship between structural and magnetic properties of cubic spinel ferrite MFe2O4 (M = Mg, Mn, Fe, Co, Ni, Cu and Zn) nanoparticles (NPs). First, a brief overview of the preparation methods yielding well‐developed NPs is given. Then, key parameters of magnetic NPs representing their structural and magnetic properties are summarized with link to the relevant methods of characterization. Peculiar features of magnetism in real systems of the NPs at atomic, single‐particle, and mesoscopic level, respectively, are also discussed. Finally, the significant part of the chapter is devoted to the discussion of the structural and magnetic properties of the NPs in the context of the relevant preparation routes. Future outlooks in the field profiting from tailoring of the NP properties by doping or design of core‐shell spinel‐only particles are given.